Interactive PowerPoint Media Based on Problem-Based Learning on Set Material - Indah Feliya Santika; Nur Izzati (Jurnal Gantang, 2023)
The use of learning media will have an impact on increasing the motivation of students. However, the media is not the only factor determining the success of achieving learning outcomes. Learning strategies such as approaches, methods, and models will affect the success of Learning. This study aims to develop interactive PowerPoint media that utilizes problem-based Learning on the set material. This Research and Development study follows the Alessi & Trolip development model with planning, design, and development steps. At the development stage, this study only reached the alpha test stage to check media validity. Data was collected by testing the validity of the material, language, and media experts, which was carried out with the help of mathematics education lecturers and mathematics teachers at junior high schools. Data processing techniques use MSR (method of summated ratings). The validity test results by material and language experts obtained a value of 90.81%, with a very good category. It indicates that the material and language aspects of media are valid. Moreover, the media aspect validity test results in a value of 74.02%, with a good category indicating that the media is valid.